The prevalence of cardiac and hepatic iron overload in patients with kidney failure: A protocol for systematic review and meta‐analysis - Abdulqadir J. Nashwan (11659453) (2022)
Introduction Few studies have reported cardiac and hepatic iron overload in patients with kidney failure or end-stage renal disease and the current evidence regarding the prevalence is still scarce. To the best of the authors' knowledge and following an exhaustive search; no systematic review/meta-analysis has estimated the aggregated prevalence of cardiac and hepatic iron overload in this patient population. Aim This review aims to estimate the prevalence of hepatic and/or cardiac iron overload in patients with kidney failure who are receiving hemodialysis, peritoneal dialysis, or underwent kidney transplants. Methods A systematic review with meta-analysis will be conducted and reported in line with PRISMA guidelines. MEDLINE and Embase bibliographic databases will be searched using a comprehensive list of controlled vocabularies and keywords to identify relevant studies. All studies reporting the prevalence of hepatic and/or cardiac iron overload prevalence in patients with kidney failure will be considered. Risk of bias assessment for included studies will be conducted based on the study design. StataBE v17 and MetaXL v5.3 will be utilized to perform the meta-analysis. Discussion The findings of this systematic review and analysis are expected to give information on the prevalence of iron overload among patients with kidney failure, which will optimize interventions and guide future research in this understudied field. Other Information Published in: Health Science Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/hsr2.692